Balancing control of a bicycle-riding humanoid robot with center of gravity estimation. (2nd September 2018) - Huang, Chun-Feng; Tung, Yen-Chun; Lu, Hao-Tien; Yeh, T.-J.
ABSTRACT: In this research, a miniaturized humanoid robot is constructed to ride and pedal a bicycle of comparable size. The design of the controller for the robot to balance and steer the bicycle using the handlebar is of particular interest. The controller possesses the capability to estimate the uncertain center of gravity of the robot-bicycle system and then incorporate such an estimation to enhance control performance. A general control framework which can achieve asymptotic stability under uncertain measurement biases is adopted for controller design. Using the framework, the stability of the control system is analytically guaranteed and its control parameters can be determined in a systematic manner. Both simulations and experiments verify that the proposed controller can automatically counteract the mass imbalance in the robot-bicycle system and allow it to perform straight-line steering without using camera visual feedback. GRAPHICAL ABSTRACT: